Developing personas and proto personas to enhance the art museum visitor experience - Luz, F. G. da.; Ferreira, P. A. (Keep it Simple Make it Fast! DIY cultures and global challenges: Book of abstracts, 2021)
This paper aims to study and think about the use of personas and proto personas on the art museum visitors experience. Its object of study is the educational services of art museums focusing on children and young people up to the age of 18. This is a hybrid study - conceptual and empirical – and exploratory study. It was conducted through a qualitative methodology, constructivist paradigm and design approach. It relies on critical and creative thinking, as well on data collection. Using a total of 36 interviews to teachers/educators and children guardians, divided into 2 distinct phases, and a total of 3 pre-test interviews. This paper allowed to draw five conclusions. First, building personas enables the art museum to understand its audience. Visitor’s needs and objectives can be assessed in a more direct and efficient way by adapting designing strategies. Second, they are the basis for redesigning: the museum space, the visitor's journey and the visitor's experience. Third, personas allow to simulate a visitor model with differentiating profiles. Fourth, proto personas are created through brainstorming about the visitors, allowing to generate tools to start the early planning with a lower budget. Significant costs may be reduced and changes to management practices applied. Fifth, providing insights for the construction of a space for creative expression and nonformal education based on the visual arts aimed at children and young people up to the age of 18. This paper expands the investigation of application of the construction of personas and proto personas in the management of educational services in art museums. The value of this study lies in exploration of the construction of personas and in a learning context Do - Feel - Learn instead of the traditional sequence Learn - Feel - Do.